Drill and Plow Machine - Sama Abosair, Fatima Zhraa Raeq Saidi; Fatima Zhraa Raeq Saidi (My University, 2024)
This project focuses on developing a robot designed to assist farmers in ploughing and digging tasks, reducing the physical stress associated with manual labor, especially during extreme weather conditions. The robot is equipped with a plough and a digging tool and is powered by lithiumion batteries. It operates through an application that provides two basic modes of operation: an autonomous ploughing mode where the robot ploughs the soil while avoiding obstacles, and a ploughing and digging mode that allows the farmer to have full control over the robot’s movements. The digging mode also allows for precise control of the digging operations. In addition, the robot was tested in real field conditions, showing a significant reduction in the physical effort required from farmers and an improvement in the efficiency of ploughing and digging.